25‐year weight gain in a racially balanced sample of U.S. adults: The CARDIA study. Issue 9 (September 2016) - Dutton, Gareth R.; Kim, Yongin; Jacobs, David R.; Li, Xuelin; Loria, Catherine M.; Reis, Jared P.; Carnethon, Mercedes; Durant, Nefertiti H.; Gordon‐Larsen, Penny; Shikany, James M.; Sidney, Stephen; Lewis, Cora E.
Abstract : Objective: To examine 25‐year trends in weight gain, partitioned by time‐related and aging‐related changes, during early and middle adulthood. Methods: Coronary Artery Risk Development in Young Adults (CARDIA), a prospective, non‐nationally representative cohort study conducted at four urban field centers that began in 1985 to 1986 with 5, 109 Black (B) and White (W) men (M) and women (W) aged 18 to 30 years, has followed participants for 25 years (aged 43–55 years in 2010–2011). Time‐related and aging‐related components of weight change were estimated to construct longitudinal models of linear and nonlinear trends. Results: There were nonlinear trends in time‐related weight gain in W, with larger weight gains early that attenuated at subsequent exams. Time‐related trends were linear in M. There were nonlinear trends in aging‐related weight gain in BM, BW, and WM, with the greatest weight gains at younger ages. Aging‐related trends were linear in WW. Participants with overweight or obesity in early adulthood had greater attenuation of aging‐related weight gain during middle adulthood. Conclusions: These findings partially support recent surveys indicating slower increases in obesity prevalence in recent years. Findings further suggest that aging‐related weight gain is greatest in the 20s and may begin attenuating as early as the mid‐30s among some groups.